Quality characterization of honey from Philippine narra (Pterocarpus indicus) - Nolasco, Norie Anne B.; Azanza, Ma. Patricia (2007., 2007)
The present study established the quality characteristics of raw honey from Philippine narra (Pterocarpus indicus) based on their physico-chemical, microbial, chemical, sensory and floral origin. Raw narra honey was evaluated to have the following characteristics: extra light amber color with mean values of pH 3.41, 0.62 Aw, 18% moisture content and 81.6°Bx soluble solids. The mean TPC, YMC and presumptive coliform count values of 3.9x10^3 cfu/g, 2.4x10^3 cfu/g and 1.7x10^1 MPN/g applying isolation methods using selective media modified with the addition of 50% sucrose (w/w) were established. Raw narra honey was shown to contain 35.98% glucose, 41.90% fructose and 3.31% sucrose. Using Head Space-SPME-GC Analysis, 18 volatile compounds were identified in raw narra honey by GC-MS analysis including 5-hydroxynonaoic acid lactone, dodecanoic acid, undecanoic acid, dihydro-5-pentenyl-2(3H)-furanone, decanoic acid, 5-hexyldihydro-2(3H)-furanone, nonanoic acid, dihydro-5-heptyl-2(3H)-furanone, 11-octadecenal, dihydro-5-pentenyl-2(3H)-furanone, heptanoic acid, octanoic acid, hexanoic acid, 2-undecenal, tetradecenal, undecenal, benzaldehyde and 2 or 3-furaldehyde. The established sensory attributes of raw narra honey were: highly viscous liquid with distinct yellow color of high clarity; intense sweet taste with slight sour and bitter tastes; no note of saltiness with detectable burnt, fruity, raisin and yeasty aroma, as well as, medicinal and brandy flavors. The dominant type of pollens present in raw narra honey with 98.82% relative pollen frequency matched the external morphology and pollen diameter (20µ) of the pollens from fresh narra flowers, those artificially spiked stored raw narra honey and that of the reference pollen P. indicus, PNH575 as determined by pollen frequency analysis. Pasteurization schedule of 77°C for 2 min and rapidly cooled to about 54°C was shown to effect a decrease of 11.1%, 24% and 11.76% in TPC, YMC and presumptive coliform count respectively. It was also shown that pasteurization of narra honey did not affect the physico-chemical and sensory properties of raw narra honey since there were no significant differences relative to raw narra honey at 5% level of significance. Determination of flavonoids as markers of authenticity was recommended for further stu
Thesis (Ph.D. Food Science)--University of the Philippines Diliman
Keywords: Honey